Polish Migration’s Socio-Cultural Impact on Wales in the Aftermath of 2004 – Preliminary Findings from Western Wales: An Aberystwyth Case Study - Wróbel, Paweł (Studia Celtica Posnaniensia, 2016)
This papers looks at the societal and cultural impact of the post-2004 Polish migration to Wales. The history of Polish migration to the UK is introduced together with the relevant statistics and their rationale behind choosing cosmopolitan Wales as their new country of residence. Even though the focus of the paper is rather on the UK as a whole, it is Wales that is central to the investigation. Wales was particularly neglected in the study of migration in the aftermath of the 2004 European Union (EU) enlargement and surprisingly little attention was given to it. Focusing on Polish diaspora is important as it is the most numerous external migration wave to Wales (ONS 2011). The case study of Aberystwyth is introduced as a good example of a semi-urban area to which Poles migrated after 2004. Moreover, the paper elaborates on the characteristics of the Polish newcomers by analysing their distinctive features, migration patterns as well as adaptation processes. Mutual relations between post-1945 and post-2004 immigration waves are investigated, together with Poles’ own image and perception. This paper gives a deeper understanding and provides an insight into the nature of the Polish migrants’ impact on the cultural and societal life of Wales.